Effect of Different Levels of Spice Mixture and Salt on the Preparation of Semi-dried Fish Sausages - V.R., Joshi; T.M., Rudra Setty (Fishery Technology, 2025)
Fermented semi-dry fish sausages were prepared with different levels of spice mixture (1 to 3.0%) and salt (1.5 to 3.5%) and were subjected to chemical and organoleptic evaluation. Different levels of spice mixture did not have any significant effect on the rate of fermentation and 2.5% level of spice mixture was preferred by the panelists. Increased salt levels delayed fermentation rate and 3% salt level was preferred by the panelists.